HUBUNGAN ANTARA KEMAMPUAN PENALARAN FORMAL DAN MOTIVASI BELAJAR FISIKA TERHADAP HASIL BELAJAR FISIKA SISWA SMPN 19 BULUKUMBA KABUPATEN BULUKUMBA - Rambega, Ulfa Laela (Jurnal Sains dan Pendidikan Fisika, 2016)
This study was an ex-post facto research aimed: (1) to obtain an empirical overview of formal reasoning ability of students, learning motivation and learning outcomes physics physics class VIII SMPN 19 Bulukumba, Bulukumba district. (2) to determine whether there is a significant relationship between formal reasoning abilities of students in the learning process to learning outcomes physics physics class VIII SMPN 19 Bulukumba, Bulukumba district. (3) to determine whether there is a significant relationship between motivation to learn physics student learning outcomes physics class VIII SMPN 19 Bulukumba, Bulukumba district. (4) to determine whether there is a significant correlation between the ability of formal reasoning in the learning process of physics motivation to learn physics class VIII SMPN 19 Bulukumba district Bulukumba and (5) to determine whether there is a significant correlation between the ability of formal reasoning in the learning process physics and motivation to learn physics student learning outcomes physics class VIII SMPN 19 Bulukumba, Bulukumba districts. The population in this study were students of class VIII SMPN 19 Bulukumba which consists of seven classes, namely class class VIIIA to VIIIG.Key words: learning outcome, formal reasoning, learning motivationPenelitian ini merupakan penelitian ex-post facto yang bertujuan;(1) Untuk mendapatkan gambaran empiris tentang kemampuan penalaran formal siswa, motivasi belajar fisika dan hasil belajar fisika siswa kelas VIII SMPN 19 Bulukumba kabupaten Bulukumba. (2) Untuk mengetahui ada tidaknya hubungan yang signifikan antara kemampuan penalaran formal siswa dalam proses pembelajaran fisika dengan hasil belajar fisika siswa kelas VIII SMPN 19 Bulukumba kabupaten Bulukumba. (3) Untuk mengetahui ada tidaknya hubungan yang signifikan antara motivasi belajar Fisika siswa dengan hasil belajar fisika siswa kelas VIII SMPN 19 Bulukumba kabupaten Bulukumba. (4) Untuk mengetahui ada tidaknya hubungan yang signifikan antara kemampuan penalaran formal siswa dalam proses pembelajaran fisika dengan motivasi belajar fisika siswa kelas VIII SMPN 19 Bulukumba kabupaten Bulukumba dan (5) Untuk mengetahui ada tidaknya hubungan yang signifikan antara kemampuan penalaran formal siswa dalam proses pembelajaran fisika dan motivasi belajar fisika siswa dengan hasil belajar fisika siswa kelas VIII SMPN 19 Bulukumba kabupaten BulukumbaÂ  secara bersama-sama.Populasi dalam penelitian ini adalah peserta didik kelas VIII SMPN 19 Bulukumba yang terdiri dari 7 kelas yaitu kelas VIIIAsampai kelas VIIIG.Kata Kunci:Â  hasil belajar, penalaran formal, motivasi belajarÂ